Analisis Teoritik Atas Tulisan Geertz Tentang Kyai Jawa Sebagai Cultural Broker - Moch. Muwaffiqillah (Institut Agama Islam Tribakti (IAIT) Kediri, 2023)
This journal article aims to conduct a theoretical analysis of Geertz's article entitled